OSCER state of the Center - (:unkn) unknown (My University, 2014)
Talk Abstract The OU Supercomputing Center for Education & Research (OSCER) celebrated its 13th anniversary on August 31 2014. In this report, we examine what OSCER is, what OSCER does, what OSCER has accomplished in its 13 years, and where OSCER is going.
Dr. Henry Neeman Assistant Vice President/Research Strategy Advisor Information Technology Director OU Supercomputing Center for Education & Research (OSCER) Information Technology Associate Professor College of Engineering Adjunct Associate Professor School of Computer Science University of Oklahoma
Presented at the Oklahoma Supercomputing Symposium 2014, September 24, 2014.
Keywords: Computation laboratories -- Oklahoma -- Norman; Cyberinfrastructure -- Oklahoma; OU Supercomputing Center for Education & Research